(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
Uncertainty research has gained increasing importance in economic policy in light of the volatility of the global economy, due to the increased uncertainty resulting from geopolitical events, global crises, and regulatory changes. Economic uncertainty reflects a state of ambiguity and difficulty in predicting future economic conditions, and includes fluctuations in economic and institutional variables. Therefore, this research analyzed the dynamics of the economic uncertainty index in Syria for the period (1997–2022), by re-measuring and improving the economic policy uncertainty index used in the study of AL-Akkari (2021), based on updated annual economic, trade, monetary, and institutional data, using the Bayesian Stochastic Volatility Model (BSVM) based on the statistical software R. The results showed that the uncertainty index witnessed sharp increases during major political and economic crises such as (the global financial crisis, the Syrian revolution, and economic sanctions), which confirms the impact of shocks on the economic and investment decision-making environment. The MAE and RMSE results also demonstrated the statistical superiority of the improved index, making it a more reliable tool for analyzing the dynamics of economic uncertainty in Syria.